US hegemonic leadership and its geopolitical codes - Naji, Saeid; Jawan, Jayum (Center for Promoting Ideas, 2011)
This paper seeks to explore the relationship between geopolitical codes and hegemonic cycles as two crucial concepts in the context of the geopolitical world order. The US geopolitical codes are analyzed in different stages of the US hegemonic cycle. The US has been selected because it is the most notable, unique case and the last hegemonic power in recent time. This analysis covers the period of the emergence of the US as a hegemonic power until its decline. This paper concludes that there is a strong relation between the two important concepts, namely geopolitical codes and hegemonic cycles and this conclusion is arrived at by analyzing the characteristics of hegemonic powers of the United States.